INGLIZCHA - O‘ZBEKCHA LUG‘AT TUZUSH MASALALARI VA ISTIQBOLLAR - Ruzimov, Sh. (SCIENCE and SOCIETY, 2021)
In this article compiling principles of U. Isaqov, M. Rahimov, B. Sobirov, S. Temirov, Sh. Isaqov’s English-Uzbek dictionaries were investigated and shown their advantages and disadvantages with examples and practical recommendations for improving compiling principles of the next generation of dictionaries were worked out.